Molecular surveillance of the Plasmodium vivax multidrug resistance 1 gene in Peru between 2006 and 2015 - Villena, Fredy E. (2020)
Background: The high incidence of Plasmodium vivax infections associated with clinical severity and the emergence of chloroquine (CQ) resistance has posed a challenge to control efforts aimed at eliminating this disease. Despite conflicting evidence regarding the role of mutations of P. vivax multidrug resistance 1 gene (pvmdr1) in drug resistance, this gene can be a tool for molecular surveillance due to its variability and spatial patterns. Methods: Blood samples were collected from studies conducted between 2006 and 2015 in the Northern and Southern Amazon Basin and the North Coast of Peru. Thick and thin blood smears were prepared for malaria diagnosis by microscopy and PCR was performed for detection of P. vivax monoinfections. The pvmdr1 gene was subsequently sequenced and the genetic data was used for haplotype and diversity analysis. Results: A total of 550 positive P. vivax samples were sequenced; 445 from the Northern Amazon Basin, 48 from the Southern Amazon Basin and 57 from the North Coast. Eight non-synonymous mutations and three synonymous mutations were analysed in 4,395 bp of pvmdr1. Amino acid changes at positions 976F and 1076L were detected in the Northern Amazon Basin (12.8%) and the Southern Amazon Basin (4.2%) with fluctuations in the prevalence of both mutations in the Northern Amazon Basin during the course of the study that seemed to correspond with a malaria control programme implemented in the region. A total of 13 pvmdr1 haplotypes with non-synonymous mutations were estimated in Peru and an overall nucleotide diversity of π = 0.00054. The Northern Amazon Basin was the most diverse region (π = 0.00055) followed by the Southern Amazon and the North Coast (π = 0.00035 and π = 0.00014, respectively). Conclusion: This study showed a high variability in the frequencies of the 976F and 1076L polymorphisms in the Northern Amazon Basin between 2006 and 2015. The low and heterogeneous diversity of pvmdr1 found in this study underscores the need for additional research that can elucidate the role of this gene on P. vivax drug resistance as well as in vitro and clinical data that can clarify the extend of CQ resistance in Peru. © 2020, The Author(s).